Is Exposure to Famine in Childhood and Economic Development in Adulthood Associated With Diabetes? - Wang, Ningjian; Wang, Xiaojin; Han, Bing; Li, Qin; Chen, Yi; Zhu, Chunfang; Chen, Yingchao; Xia, Fangzhen; Cang, Zhen; Zhu, Chaoxia; Lu, Meng; Meng, Ying; et al. (The journal of clinical endocrinology and metabolism, 2015)
Context:The Chinese were afflicted by great famine between 1959 and 1962. These people then experienced rapid economic development during which the gross domestic product per capita increased from $28 in 1978 to $6807 in 2013. We hypothesize that these two events are associated with the booming rate of diabetes in China.Objective:We aimed to explore whether exposure to famine in early life and high economic status in adulthood was associated with diabetes in later life.Design and Setting:Our data of 6897 adults were from a cross-sectional Survey on Prevalence in East China for Metabolic Diseases and Risk Factors study in 2014. Among them, 3844 adults experienced famine during different life stages and then lived in areas with different economic statuses in adulthood.Main Outcome Measure:Diabetes was considered as fasting plasma glucose of 7.0mmol/L or greater, hemoglobin A1c of 6.5% or greater, and/or a previous diagnosis by health care professionals.Results:Compared with nonexposed subjects, famine exposure during the fetal period (odds ratio [OR]1.53, 95% confidence interval [CI]1.09–2.14) and childhood (OR 1.82, 95% CI 1.21–2.73) was associated with diabetes after adjusting for age and gender. Further adjustments for adiposity, height, the lipid profile, and blood pressure did not significantly attenuate this association. Subjects living in areas with high economic status had a greater diabetes risk in adulthood (OR 1.46, 95% CI 1.20–1.78). In gender-specific analyses, fetal-exposed men (OR 1.64, 95% CI, 1.04–2.59) and childhood-exposed women (OR 2.81, 95% CI, 1.59–4.97) had significantly greater risk of diabetes.Conclusions:The rapid increase in the prevalence of diabetes in middle-aged and elderly people in China is associated with the combination of exposure to famine during the fetal stage and childhood and high economic status in adulthood. Our findings may partly explain the booming diabetes phenomenon in China.